Sustainable Finance: A Strategy to Increase Good Corporate Governance and Company Value in Banking Industry - Muhammad Tafsir (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This paper aims to examine the effect of sustainable finance on the implementation of good corporate governance and corporate value creation. Environmental damage due to company activities is increasingly worrying. The sustainable finance policy will test the extent to which the implementation of good corporate governance is going well. The success of the sustainable finance policy will ultimately increase the company's value. The results of the analysis show that sustainable finance has a positive impact on the implementation of good corporate governance where sustainable finance will be successful if corporate governance is well implemented, as well as corporate value, where investors or the public will have a positive influence on the company's seriousness in implementing financial programs. sustainable and corporate value. This study is hoped to be an input for the government and banks in supporting environmental protection.